Transcriptome Profiling of Taproot Reveals Complex Regulatory Networks during Taproot Thickening in Radish (Raphanus sativus L.) - Yu, Rugang; Wang, Jing; Xu, Liang; Wang, Yan; Wang, Ronghua; Zhu, Xianwen; Sun, Xiaochuan; Luo, Xiaobo; Xie, Yang; Everlyne, Muleke; Liu, Liwang (Frontiers in Plant Science, 2016)
Radish (Raphanus sativus L.,) is one of the most important vegetable crops worldwide. Taproot thickening represents a critical developmental period that determines yield and quality in radish life cycle. To isolate differentially expressed genes (DGEs) involved in radish taproot thickening process and explored the molecular mechanism in underlying taproot development, three cDNA libraries from radish taproot collected at pre-cortex splitting stage (L1), cortex splitting stage (L2) and expanding stage (L3) were constructed and sequenced by RNA-Seq technology. More than seven million clean reads were obtained from the three libraries, respectively, from which 4,717,617 (L1, 65.35%), 4,809,588 (L2, 68.24%) and 4,973,745 (L3, 69.45%) reads were matched to the radish reference genes. A total of 85,939 transcripts were generated from three libraries, from which 10,450, 12,325 and 7,392 differentially expressed transcripts (DETs) were detected in L1 vs. L2, L1 vs. L3, and L2 vs. L3 comparisons, respectively. Gene Ontology and pathway analysis showed that many DEGs, including EXPA9, Cyclin, CaM, Syntaxin, MADS-box, SAUR and CalS were involved in cell events, cell wall modification, regulation of plant hormone levels, signal transduction and metabolisms, which may relate to taproot thickening. Furthermore, the integrated analysis of mRNA-miRNA revealed that 43 miRNAs and 92 genes that formed 114 miRNA-target mRNA pairs were co-expressed, and three miRNA-target regulatory networks of taproot were constructed from different libraries. Finally, the expression patterns of 16 selected genes were confirmed using RT-qPCR analysis. A hypothetical model of genetic regulatory network associated with taproot thickening in radish was put forward. The taproot formation of radish is mainly contributed to cell differentiation, division and expansion, which are regulated and promoted by certain specific signal transduction pathways and metabolism possesses. These results could provide new insights into the complex molecular mechanism underlying taproot thickening and facilitate genetic improvement of taproot in radish.